2004
DOI: 10.2113/3.2.444
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Scale Visualization of Colloid Transport and Retention in Partly Saturated Porous Media

Abstract: Wan and Wilson (1994a), colloid transport experiments with porous media have been based on mass balance In unsaturated porous media, sorption of colloids at the air-water of breakthrough colloid concentrations in packed-sand (AW) interface is accepted as a mechanism for controlling colloid retention and mobilization. However, limited actual pore-scale obser-columns (Wan and Wilson, 1994b;Schafer et al., 1998; vations of colloid attachment to the AW interface have been made. To Jewett et al., 1999; Jin et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 21 publications
10
96
3
Order By: Relevance
“…In addition, for unsaturated systems colloid retention at the stationary, Yao (1968) , Infl uence of suspended particle size on the transport aspect of water fi ltration, University of North Carolina, Chapel Hill, Dissertation. ) mobile or transitional gas -water interface has to be taken into account (Crist et al , 2004 ;Lenhart and Saiers, 2002 ;Ouyang et al , 1996 ;Wan and Tokunaga, 1997 ). While the maximum size of mobile colloids will be limited by straining fi ltration and pore velocity, concentration and size distribution of smaller colloids are controlled by physico -chemical fi ltration.…”
Section: Fate and Behaviour Of Colloids And Nanoparticles In Porous Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for unsaturated systems colloid retention at the stationary, Yao (1968) , Infl uence of suspended particle size on the transport aspect of water fi ltration, University of North Carolina, Chapel Hill, Dissertation. ) mobile or transitional gas -water interface has to be taken into account (Crist et al , 2004 ;Lenhart and Saiers, 2002 ;Ouyang et al , 1996 ;Wan and Tokunaga, 1997 ). While the maximum size of mobile colloids will be limited by straining fi ltration and pore velocity, concentration and size distribution of smaller colloids are controlled by physico -chemical fi ltration.…”
Section: Fate and Behaviour Of Colloids And Nanoparticles In Porous Mmentioning
confidence: 99%
“…There, the liquid -gas interface can act as barrier for colloid movement if the water fi lm in the unsaturated media is thinner than the diameter of the colloids. Colloids can also be retained at the menisci of pendular rings of the fl uid -gas collector interface instead of the liquid -gas interface (Crist et al , 2004 ). Consequently, calculations using equations from the CFT for an unsaturated soil system should be regarded with care and can serve, if at all, only as a fi rst rough estimation.…”
Section: Unsaturated Porous Mediamentioning
confidence: 99%
“…Water films surrounding solid grains may be as thin as tens of nanometers (36,45), close to or smaller than the size of most of colloids and nanomaterials. As such, film straining is believed to be at least as important as air-water interface attachment in unsaturated transport (27,32,34,35,(45)(46)(47)(48)(49)(50). Studies with bacteria (34,35), silica colloids (27), and latex microspheres (47)(48)(49)(50)(51) have suggested that film straining may be the dominant mechanism in immobilizing colloids during unsaturated transport in many systems.…”
Section: Transport Of Colloids and Nanomaterials In Unsaturated Poroumentioning
confidence: 99%
“…As such, film straining is believed to be at least as important as air-water interface attachment in unsaturated transport (27,32,34,35,(45)(46)(47)(48)(49)(50). Studies with bacteria (34,35), silica colloids (27), and latex microspheres (47)(48)(49)(50)(51) have suggested that film straining may be the dominant mechanism in immobilizing colloids during unsaturated transport in many systems. Through microscope visualization in thin sand chambers, negatively charged hydrophilic latex has been reported to be mainly retained by the air-water-solid contact line, but not by thin water films or the air-water interface (47)(48)(49)(50).…”
Section: Transport Of Colloids and Nanomaterials In Unsaturated Poroumentioning
confidence: 99%
See 1 more Smart Citation